Profile comorbidity and impact of insomnia in the Ibadan (2009)
Objective: To provide information on the profile, comorbidity and impact of insomnia among an understudied group of elderly Africans. Method: Using the WHO Composite International Diagnostic Interview (CIDI), the 12-month prevalence of three forms of insomnia was assessed in face-to-face interviews conducted with a regionally-representative sample of elderly Nigerians, aged 65 years and over (n=2152). The association of insomnia with quality of life, rated with the WHO Quality of Life instrument, was analyzed controlling for comorbid chronic pain, chronic medical conditions and DSM-IV major depressive disorder. Results: At least one insomnia problem was reported by 30.72%. Insomnia was more frequent among females, persons aged 70 years and over, and those who were unmarried. Insomnia was comorbid with major depressive disorder (OR = 3.9, 95% CI 2.5 – 6.1), chronic pain (OR = 4.3, 95% CI 3.2 – 6.1; particularly arthritis and spinal pain), and chronic medical conditions (OR = 2.1, 95% CI 1.8 – 2.5, particularly heart disease, high blood pressure or asthma). Persons with insomnia were more likely to report having had a fall in the previous year (OR = 1.4, 95% CI 1.0 –1.8) and, among those with fall, injury was more commonly reported by those with insomnia. Every form of insomnia was associated with decrement in quality of life. After controlling for comorbid mental and physical conditions, the β coefficients ranged between −17.9 and −20.0. Conclusion: Insomnia was highly comorbid with chronic physical conditions and with depression. These comorbid conditions partly but do not entirely account for the considerable decrement in quality of life associated with insomnia.